Identification of BACE2 as an avid ß-amyloid-degrading protease - Abdul-Hay, Samer O (BioMed Central, 2012)
BACKGROUND: Proteases that degrade the amyloid ß-protein (Aß) have emerged as key players in the etiology and potential treatment of Alzheimer’s disease (AD), but it is unlikely that all such proteases have been identified. To discover new Aß-degrading proteases (AßDPs), we conducted an unbiased, genome-scale, functional cDNA screen designed to identify proteases capable of lowering net Aß levels produced by cells, which were subsequently characterized for Aß-degrading activity using an array of downstream assays. RESULTS: The top hit emerging from the screen was ß-site amyloid precursor protein-cleaving enzyme 2 (BACE2), a rather unexpected finding given the well-established role of its close homolog, BACE1, in the production of Aß. BACE2 is known to be capable of lowering Aß levels via non-amyloidogenic processing of APP. However, in vitro, BACE2 was also found to be a particularly avid AßDP, with a catalytic efficiency exceeding all known AßDPs except insulin-degrading enzyme (IDE). BACE1 was also found to degrade Aß, albeit ~150-fold less efficiently than BACE2. Aß is cleaved by BACE2 at three peptide bonds—Phe19-Phe20, Phe20-Ala21, and Leu34-Met35—with the latter cleavage site being the initial and principal one. BACE2 overexpression in cultured cells was found to lower net Aß levels to a greater extent than multiple, well-established AßDPs, including neprilysin (NEP) and endothelin-converting enzyme-1 (ECE1), while showing comparable effectiveness to IDE. CONCLUSIONS: This study identifies a new functional role for BACE2 as a potent AßDP. Based on its high catalytic efficiency, its ability to degrade Aß intracellularly, and other characteristics, BACE2 represents a particulary strong therapeutic candidate for the treatment or prevention of AD.